Suppressing Mo‐Species Leaching in MoOx/A‐Ni3S2 Cathode for Stable Anion Exchange Membrane Water Electrolysis at Industrial‐Scale Current Density - Husileng Lee; Guoheng Ding; Linqin Wang; Yunxuan Ding; Tang Tang; Licheng Sun (Advanced Science, 2025)
Abstract The development of non‐noble metal‐based hydrogen evolving reaction (HER) electrocatalysts operating under high current density plays a critical role in the large‐scale application of anion exchange membrane water electrolysis (AEM‐WE). Herein, a porous and hybrid MoS2/Ni3S2 is synthesized on nickel foam (NF) via a one‐step hydrothermal method and studied its reconstruction process during alkaline HER conditions. Experimental results indicated that the MoS2 underwent an oxidative dissolution followed by a dynamic equilibrium between dissolution and redeposition of the amorphous MoOx during HER. Meanwhile, S‐vacancy‐rich Ni3S2 (A‐Ni3S2) is exposed and acts as the real active site for HER. The obtained MoOx/A‐Ni3S2 catalyst exhibited high catalytic performance in three‐electrode systems and single‐cell AEM‐WE. Finally, for a long‐term durability test in the AEM electrolyzer, a dry cathode method is applied to suppress the Mo species leaching from the MoOx/A‐Ni3S2 electrode. Remarkably, the device assembled by MoOx/A‐Ni3S2 as the cathode catalyst and NiFe as the anode catalyst demonstrated a high stability of 2500 h at 2 A cm−2 and 40 °C with a small aging rate of 30 µV h−1.